Alternatives of the multiple use of Virginia mallow (Sida hermaphrodita L. Rusby) as a shrub-replacing mallow in the temperate climate zone - Kurucz, Erika; Szarvas, Pál; Fári, Miklós Gábor (Acta Agraria Debreceniensis, 2012)
In the seventies of the previous century, Dr. Zoltán Kováts set two directions in the research of mallows. One of the directions was the biotechnology of the mallow species and the other direction is using the mallow species as biomass material. In order to do this he brought mallow mother spawns of ornamental and biomass sorts from botanical gardens abroad and tested many of them, including the a Sida hermaphrodita kind. Fourty years later, for the second time this plant, known as the „energy mallow” got back to Hungary again, right into the sight of hungarian biomass business with the help of László Balogh and his associates using help from Poland. This genus got into the center of our research, because of it’s valuable attributes. The latest experiments are about using it as an energy plant, without examining genetic details. The plant grows up to morethan 3 meters, has high growing rate and produces big amount of green mass. We don’t have any hungarian data about whether the plant continues the sufficient growing rate or not, after cutting it back.We have to explore the potentials in the Sida’s sublimation. The plant is mostly suitable for ornamental and energy utilization, so further sublimation should be aiming for these aspects. During my research period, we are willing to get to know these potentials and the best possible use of them.